Isolation and Purification of Murine Microglial Cells for Flow Cytometry - Peter Theriault; Maude Bordeleau; Serge Rivest (Bio-Protocol, 2016)
The detailed protocol is used to isolate different cell types from murine brain as glial cells, including microglia, using an enzymatic digestion that minimizes cellular mortality. A Percoll gradient (30% to 80%) separation allows a maximal recovery of isolated murine microglial cells prior to flow cytometry analysis.